Toxic Positivity dalam Lagu Senyuman & Harapan: Perspektif Tasawuf - Azka Amalia; Dafa Alpahriza; Inry Aprilia; M. Zia Al-Haromain; Dadan Firdaus (Indo Publishing, 2026)
The phenomenon of toxic positivity is increasingly prevalent in modern society through various forms of communication and popular culture that encourage individuals to always maintain a positive attitude. This situation risks disregarding negative emotions, which are in fact a natural part of the human experience. This study aims to identify representations of toxic positivity in the lyrics of the song ‘Senyuman & Harapan’ by GAC and to analysethem through a Sufi perspective. The subject of this study is the lyrics of the song ‘Senyuman & Harapan’ by GAC. The study utilises the theory of toxic positivity by Whitney Goodman, as well as Al-Ghazali’s concepts of emotion regulation and patience, as the basis for its analysis. This study employs a qualitative approach using a descriptive-analytical method. Data were collected through a literature review and textual analysis of the song lyrics. The results indicate that the lyrics of the song ‘Senyuman & Harapan’ exhibit several indicators of toxic positivity, particularly the enforcement of a positive attitude and the suppression of negative emotions through the dominance of optimistic messages. From a Sufi perspective, the concept of patience does not reject negative emotions, but rather teaches the acceptance and management of emotions in a conscious manner through a spiritual approach. This study concludes that the message of optimism in the song can be understood as a form of positive motivation, but has the potential to lead to toxic positivity if it disregards the existence of negative emotions and the process of managing them.